1999
DOI: 10.1046/j.1365-294x.1999.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in clonal diversity in glasshouse infestations of the aphid, Aphis gossypii Glover in southern France

Abstract: Aphis gossypii is an aphid species that is found throughout the world and is extremely polyphagous. It is considered a major pest of cotton and cucurbit species. In Europe, A. gossypii is assumed to reproduce exclusively by apomictic parthenogenesis. The present study investigates the genetic diversity of A. gossypii in a microgeographic, fragmented habitat consisting of eight glasshouses of cucurbit crops. This analysis, which was based on the results from seven microsatellite loci, has confirmed that A. goss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 48 publications
7
84
0
1
Order By: Relevance
“…This indicates that the majority of the Australian populations of grape phylloxera are comprised of functionally parthenogenetic lineages. The heterozygous nature of these classes at several loci is consistent with previous observations of other primarily parthenogenetic aphid populations (Fuller et al, 1999;Simon et al, 1999). Reproduction by parthenogenesis in these lineages is supported by the absence of expected recombinant genotypes, such as individuals that are homozygous for the DVIT1 128 allele and significant deviation from Hardy-Weinberg equilibrium for all loci (Table 4).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This indicates that the majority of the Australian populations of grape phylloxera are comprised of functionally parthenogenetic lineages. The heterozygous nature of these classes at several loci is consistent with previous observations of other primarily parthenogenetic aphid populations (Fuller et al, 1999;Simon et al, 1999). Reproduction by parthenogenesis in these lineages is supported by the absence of expected recombinant genotypes, such as individuals that are homozygous for the DVIT1 128 allele and significant deviation from Hardy-Weinberg equilibrium for all loci (Table 4).…”
Section: Discussionsupporting
confidence: 88%
“…As codominant and highly variable DNA markers, they provide a powerful system for unraveling life history traits, particularly the occurrence of sex (reviewed in Sunnucks et al, 1997;Hales et al, 1997). They have been used in life cycle studies of members of the Aphididae family, resulting in high level resolution of reproductive mode and exploration of genetic relationships, including those of clonal lineages (Sunnucks et al, 1996Fuller et al, 1999;Simon et al, 1999;Wilson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the reduction in clonal diversity could also be the result of a competition between the two genotypes, Burk1 and Ivo , if we assume that aphids carrying Burk1 have a better performance than Ivo on cotton whatever the insecticide pressure. Fuller et al (1999) observed a significant decrease in clonal diversity over a crop season in A. gossypii populations in commercial cucumber glasshouses and competition between two Curcurbitaceae-specific genotypes of A. gossypii was experimentally demonstrated ( Rochat et al , 1999 ). Nevertheless, analysis of two A. gossypii samples collected in untreated isolated irrigated cotton fields during the dry season (Maroua, Cameroon, 14 March 2005) and in wild cotton plants (Ziguinchor, Senegal, 250 km from the cotton-growing area, 22 April 2005) revealed a predominance of the genotype Ivo , with a frequency of 95% and 100%, respectively (T. Brévault, unpublished data).…”
Section: Influence Of Insecticide Treatments and Competition Among CLmentioning
confidence: 99%
“…Several tropical and sub-tropical pests are now established in northern countries due to glasshouses (Kiritani, 2006). The patchy distribution and the enclosed environment of glasshouses are expected to induce genetic drift and decrease genetic diversity, as was observed with glasshouse populations of the native aphid Aphis gossypii in France (Fuller et al, 1999). The genetic structure of invasive pests in glasshouses outside of their native range has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%